2014
DOI: 10.1007/s00253-014-5908-z
|View full text |Cite
|
Sign up to set email alerts
|

A contribution of hydrogenotrophic methanogenesis to the biogenic coal bed methane reserves of Southern Qinshui Basin, China

Abstract: The activity of methanogens and related bacteria which inhabit the coal beds is essential for stimulating new biogenic coal bed methane (CBM) production from the coal matrix. In this study, the microbial community structure and methanogenesis were investigated in Southern Qinshui Basin in China, and the composition and stable isotopic ratios of CBM were also determined. Although geochemical analysis suggested a mainly thermogenic origin for CBM, the microbial community structure and activities strongly implied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 60 publications
4
46
0
Order By: Relevance
“…Two metabolic types of methanogenesis have been determined, involving carbon dioxide reduction or acetate fermentation. Guo et al (2014) found that carbon dioxide reduction methanogenesis is dominantly active in the Qinshui Basin. It is generally accepted that carbon dioxide reduction removes 12 C, forming positive d 13 C DIC in remaining formation water (Mori et al, 2012).…”
Section: Application Of Dissolved Inorganic Carbon Isotopic Ratio Formentioning
confidence: 98%
“…Two metabolic types of methanogenesis have been determined, involving carbon dioxide reduction or acetate fermentation. Guo et al (2014) found that carbon dioxide reduction methanogenesis is dominantly active in the Qinshui Basin. It is generally accepted that carbon dioxide reduction removes 12 C, forming positive d 13 C DIC in remaining formation water (Mori et al, 2012).…”
Section: Application Of Dissolved Inorganic Carbon Isotopic Ratio Formentioning
confidence: 98%
“…The coal sample was collected from Sihe coal mine in Qinshui basin, south-central Shanxi province, where biogenic CBM has been found and diverse microbial communities have been detected in the produced water [30]. We state no specific permissions were required for these locations/activities.…”
Section: Coal Sample and Microfloramentioning
confidence: 99%
“…The Proteobacteria represent a vast diversity of bacterial species. However, within coal reservoirs polycyclic-aromatic-hydrocarbon(PAH)-degrading α-Proteobacteria and γ-Proteobacteria, and syntrophic δ-Proteobacteria have been detected and are known to be associated with methanogens (Guo et al, 2012a(Guo et al, , 2014Meslé et al, 2013a;Penner et al, 2010). The dominance of PAH-degrading α-Proteobacteria could reflect in situ physicochemical conditions because PAHs are the main organic compound class detected in CBM produced water samples (Orem et al, 2014).…”
Section: Microbial Pathways For Coal Biodegradation and Community Commentioning
confidence: 99%